Resected thymic large cell neuroendocrine carcinoma: A case report and review of the literature. (2019) - Ogata, Shogo; Maeda, Ryo; Tomita, Masaki; Sato, Yuichiro; Ayabe, Takanori; Nakamura, Kunihide
Highlights: Large cell neuroendocrine carcinoma (LCNEC) of the thymus is an extremely rare neoplasm and has a poor prognosis. We report a surgical case of thymic LCNEC. Further accumulation of knowledge and experience is needed to elucidate the optimal therapy for thymic LCNEC. Abstract: Introduction: Large cell neuroendocrine carcinoma (LCNEC) of the thymus is an extremely rare neoplasm. Presentation of case: We report a rare case of LCNEC of the thymus in a 55-year-old woman. Her chest roentgenogram during a routine checkup revealed an abnormal shadow in the mediastinal left upper lung field. Chest computed tomography showed an anterior mediastinal mass measuring 4.8 × 4.0 cm. Positron emission tomography with 18F-fluorodeoxyglucose (FDG) showed high FDG accumulation at the lesion. To obtain a definitive diagnosis and achieve complete resection, a surgery was performed. The postoperative diagnosis was thymic LCNEC; it was classified as a Masaoka stage III tumor due to the invasion of tumor cells into the left lung. Postoperatively, the patient received adjuvant chemotherapy and survived without any signs of recurrence for 30 months after surgery. Discussion/conclusion: The detailed clinical features of thymic LCNEC remain unknown because of its rarity. In total, 20 cases of resection for LCNEC, including the present case, have been reported in the English language literature; we have presented a review of these cases and discussed the optimal therapy for this rare and virulent tumor of the thymus.